Study on generation of turbulence-distorted received signals in OAM optical communications obeying dual Johnson SBdistribution - Chunyi CHEN; Qinqin XIONG; Haiyang YU; Haifeng YAO; Jiaxue SONG; Yan LOU (Tongxin xuebao)
In order to analyze the performance of atmospheric OAM optical communication systems by Monte Carlo method,a method was proposed to simulate turbulence-distorted received signals in OAM optical communications,which possessed the given temporal auto-correlation and obeyed the dual Johnson SBdistribution.A Gaussian random sequence with given temporal auto-correlation was first created by using an auto regression (AR) model,and meanwhile a white noise random sample sequence obeying the dual Johnson SBdistribution was generated.Then the white noise random sample sequence was rearranged according to the statistical rank of the auto-correlated Gaussian random sequence to match the given temporal auto-correlation.By performing the simulation experiments,it was found that the statistical distribution of the simulated signals was in excellent agreement with the dual Johnson SBdistribution,and the temporal auto-correlation of the signals matched the given temporal auto-correlation function.The results demonstrate that the proposed method can be used to simulate time-domain received signals in OAM optical communications impaired by turbulence-induced distortions.